PENERAPAN MODEL PEMBELAJARAN TEAM ASSISTED INDIVIDUALISATION (TAI) DENGAN MEDIA VISUAL DALAM PENINGKATAN PEMBELAJARAN IPS PADA SISWA KELAS V SD NEGERI 2 KARANGSARI TAHUN AJARAN 2015/2016 - Lestari, Puput Puji (KALAM CENDEKIA PGSD KEBUMEN, 2016)
Abstract: The Application Of Team Assisted Individualization (TAI) Type Using Visual Media In Improving Social Study Learning For The FifthGrade Students Of SD. The objectives of the research collaborative Classroom Action Research (CAR) to improve social study learning for the fifth grade students of SD. This research conducted in three cycle. Each cycle consisted of two (pertemuan), there are planning, implementation, observation, and reflection. Subjects of this research were 25 students of SD Negeri 2 Karangsari in the academic year of 2015/2016. Sources of data were obtained from students, teachers, and, observers. Data collection techniques were test of learning outcomes, observation, interview, and documentation. Validity of data used triangulation techniques and triangulation of sources of data. The results of the research show that the steps of Team Assisted Individualization (TAI) type using visual media can improve social study learning for the fifth grade students of SD. The results of the research show that persentage of the students completed from initial condicition is 36,00% to 88,00% in the last of third cycle.Keywords: TAI, Visual media, Social study learning Abstrak: Penerapan Model Pembelajaran Team Assisted Individualisation (TAI) dengan Media Visual dalam Peningkatan Pembelajaran IPS pada Siswa Kelas V SD. Tujuan Penelitian Tindakan Kelas (PTK) kolaboratif ini adalah untuk meningkatkan pembelajaran IPS pada siswa kelas V SD. Penelitian ini dilaksanakan dalam tiga siklus. Masing-masing siklus terdapat dua pertemuan yang terdiri dari tahap perencanaan, pelaksanaan, pelaksanaan, pengamatan, dan refleksi. Subjek penelitian ini adalah siswa kelas V SD Negeri 2 Karangsari yang berjumlah 25 siswa. Sumber data berasal dari guru kelas, siswa, dan dokumen. Teknik pengumpulan data menggunakan teknik tes, observasi, wawancara, dan dokumentasi. Validasi data menggunakan triangulasi teknik dan triangulasi sumber. Hasil penelitian menunjukkan bahwa penerapan langkah-langkah model TAI dengan media visual dapat meningkatkan pembelajaran IPS pada siswa kelas V SD. Hasil penelitian, menunjukkan bahwa persentase siswa tuntas mengalami peningkatan dari kondisi awal 36,00% meningkat menjadi 88,00% pada pertemuan akhir siklus III.Kata kunci: TAI, media visual, pembelajaran IPS